Moving Image Learning Integrated Problem-Based Interactive Media to Improve Students' Critical Thinking - Muhammad, Fahreza Aulia; Sudiyanto; Ardianto, Deny Tri (Jurnal Pendidikan dan Pengajaran, 2024)
The enormous potential of using digital teaching materials in interactive media format is a promising solution for improving 21st century skills for vocational high school students. Therefore, this research aims to create problem-based interactive learning media to improve the critical thinking skills of vocational high school students. Using research and development methods with the Alessi & Trollip model, the subjects of this research included one media expert, one material expert, three teachers and 28 students. Data collection was carried out through observation, interviews and questionnaires, analyzed qualitatively and quantitatively using instruments consisting of observation sheets, lists of questions and questionnaires. In general, the results of this research succeeded in creating interactive learning media which is included in the appropriate category based on validation results by media experts, material experts and practitioners. And the results of the practicality assessment by students also obtained decent results. Apart from that, the interactive learning media developed was also proven to be effective in improving students' critical thinking skills as seen through the experimental class's average score of 86.73, higher than the control class, indicating that this media is effective in improving critical thinking skills. It is hoped that this research can become a reference for teachers to implement interactive media-based in order to improve students' critical thinking skills, especially in learning Light Moving Images in vocational schools.